INTERPRETATION OF VIEWS ON ANCIENT TURKISH MYTHOLOGY - Qarshiyeva Shohsanam Abdurashidovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article talks about the genesis, essence and mythological motives of ancient Turkic myths. Literary-scientific views of ancient Turkic literature researchers on mythology and scientific works in this direction were studied in a historical-comparative aspect.